Effect of Zinc Oxide Nano-Particles on Motor Coordination in the Attendance of Vitamin C in Rats - Maryam Rafieirad; Saeed Valipour Chahardah Charic (Islamic Azad University, 2017)
Introduction: Zinc oxide is an inorganic compound with the formula ZnO. Oxide is widely used in various applications, especially in pharmaceutical applications, as well as technical and cosmetic products. The aim of this study is to evaluate the effect of zinc oxide nano-particles (ZnO NPs) on the motor coordination of male rats in the presence and absence of vitamin C as an antioxidant. Methods: In this experimental study, 80 male Wistar rats with a weight range of 200-250 g were used. The rats were randomly divided into ten 8-memebr groups control group (saline receivers) and rats which received zinc nano-oxide with doses 1.25, 2.5 and 5 mg/kg, rats receiving vitamin C with doses 30, 60 and 120 mg/kg and rats which received both zinc nano-oxide with doses 1.25, 2.5 and 5 mg/kg and vitamin C with a dose of 30 mg/kg.while different groups received the above doses intraperitoneally (i.p) the rate of motor coordination was measured in the first day of study using rotarod machine. Motor coordination was considered as the duration a rat could stay on the rotarod. Results: According to the results, dose dependent ZnO NPs with doses 1.25, 2.5 and 5 mg/kg and the simultaneous prescription of different doses of ZnO NPs and a neutral amount of vitamin C decrease this rotarod duration. Conclusion: ZnO NPs disturb motor coordination. Probably, this is not due to the oxidative feature of zinc because vitamin C could not improve this effect. It seems that this effect is applied by another mechanism such as changing the activities of neurochemical system contributing to motor coordination.